Personal Hygiene Practices Associated with Preventing Covid-19 in Semarang City - Deby Hizky Butarbutar; Nurjazuli Nurjazuli; Nikie Astorina Yunita Dewanti (Al-Sihah : The Public Health Science Journal, 2021)
The healthcare workers and non-healthcare workers who work in public health centers become the high-risk group infected COVID-19. One of the preventions that can be applied is personal hygiene practice. The aim of the study was to analyze factors related to personal hygiene practice in healthcare workers and non-healthcare workers in order to prevent the COVID-19 at Srondol Health Center, Semarang. The study used an analytical observational method with a cross-sectional approach, and the data were analyzed by using a chi-square test. The sample was determined by a total sampling technique with a sample of 48 workers. The study indicated that the majority of respondents who worked in the health sector (77,1%), had a good category of personal hygiene practice 54,2% and possessed a good category of personal hygiene knowledge 60,4%. There was a significant correlation between knowledge (p-value <0,05), field of work (p-value 0,041), training (p-value <0,05) and personal hygiene practice. In conclusion, factors related to personal hygiene practice on healthcare workers and non-healthcare workers at Srondol Health Center were knowledge, a field of work, and training. Meanwhile, the non-healthcare workers had poor personal hygiene practices so it was necessary to conduct socialization and monitor their personal hygiene by the health center management team.